Enhancing Physics Experience: VIRRE (Virtual Reality of Renewable Energy) to Increasing Concept Understanding and Learning Motivation in Secondary Education - Anggaryani, Mita; Citra, Nina Fajriyah (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2024)
This research aims to develop VR in renewable energy materials (VIRRE) to increase students’ concept understanding and learning motivation. This research used Research and Development (R&D) method through ADDIE development model. Validation was carried out to determine the feasibility of VIRRE, then implemented in secondary school students by using problem-based learning model throughout three meetings. Research data was collected through questionnaires and pretest-posttest during classroom learning. The results show that VIRRE has a validity percentage of 94.07% with very valid criteria. The effectiveness of VIRRE media in increasing students' concept understanding and learning motivation is included in medium criteria with n-gain scores of 0.52 and 0.33 respectively. Additionally, VIRRE usage in learning activities showed the most improved indicator of concept understanding and aspect of learning motivation, namely classifying and self-confidence respectively. Moreover, the result indicates that both concept understanding and learning motivation are related to each other, once students are motivated to learn the subject, they can achieve a great understanding of its concept. VIRRE received very good responses from students in aspects of learning activities, materials, and media use with average percentages of 82.22%, 82.7%, and 84.23% respectively. Thus, VR could be an alternative media learning to support educators in delivering physics materials, which are viewed as complicated concepts according to the students.